ESTIMATION OF MICROBIAL LOAD AND CHEMICAL COMPOSITION OF PASTEURIZED MILK FROM MARKETS IN KHARTOUM NORTH, SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to determine the effect of storage conditions on the quality of pasteurized milk distributed in Khartoum North by three companies. Sixty samples were collected from the product of each company and subjected to chemical analysis and microbiological examination in the third and fifth day of processing.The results revealed significant (P